(untitled) (Periphērica, 2020)
In his film Conducta (Behavior 2014), Ernesto Daranas portrays the ethical and physical challenges of an aging teacher, struggling to improve the lives of her students, not just within the classroom setting, but also in their family and social spheres. Thus, in response to a top/down social structure where an unseen government exerts economic and political pressure on schools and families in crisis mode, Daranas proposes model redirecting away from Ernesto Che Guevara and back toward José Martí as a pedagogic strategy for modulating conduct expectations of elementary school children. However, because government censorship sensitizes the spoken word, the filmmaker is careful to avoid negative repercussions by letting markedly visual elements of his mise en scène reveal indiscreet, if not outright subversive views of home, school, and cityscape. Also, through a recurring wandering narrative format, Ernesto Daranas conducts a political inquiry analogous to how Radicant aesthetics exercise wandering narratives.